Predictive factors of successful rehabilitation in patients with lower limb amputation attended at a rehabilitation institute - Quezada Ponte, Elisa (2024)
Objective: To determine predictive factors of successful rehabilitation in patients with lower limb amputation who use a prosthetic device. Methods: A retrospective observational and non-probabilistic study was carried out among 70 patients who underwent transfemoral (AK) or transtibial amputation (BK) of vascular, oncologic, or traumatic origin at the Instituto Nacional de Rehabilitación “Dra. Adriana Rebaza Flores” AMISTAD PERU-JAPON, Lima-Peru, from 2018 and 2019. Patients were interviewed, and clinical charts were reviewed. Successful rehabilitation was evaluated using Houghton’s instrument. Results: 81.42% were males; the mean age was 48.76 ± 15.19 years; 35.71% had between 48 and 57 years of age. Successful rehabilitation was associated with age (p<0.01), BK amputation (p<0.001), traumatic origin (p=0.014), and absence of comorbidities (p<0.04). The only predictive factor of successful rehabilitation was BK amputation [OR=2.84, p<0.02). Conclusions: Factors associated with successful rehabilitation were age below 48 years, BK amputation, traumatic origin, and fewer comorbidities, but the only determinant was the level of amputation.